The Role of Teachers in the Implementation of Online Learning in the midst of the Covid-19 Pandemic - Agus Budiyanto (Prosiding University Research Colloquium, 2021)
Since the emergence of the COVID-19 Pandemic in all corners of the world, there havebeen changes in all fields, spreading to the education aspect. Many schools have beenclosed, the learning process is temporarily carried out online from their respective homes.Madrasah parties are required to continue to carry out learning with a process that is nolonger face-to-face in class but with online learning. The focus of this research is todescribe the teacher's role in the implementation of online learning, from planning,implementing, and evaluating learning. This study uses a qualitative descriptiveresearch model. This research was conducted at MI Muhammadiyah Butuh I Kalikajarwith the research subjects being teachers, in this case the teachers were givenquestionnaires and interviews to find out several indicators of the teacher's role, (1) theteacher's role as a learning resource, in online learning, the teacher provides learningresources , namely the theme book and program (2) the role of the teacher as ademonstrator, in this distance learning where the teacher provides facilities such asmedia to assist students in the learning process; (3) the teacher's role as a motivator, theteacher provides motivation to students. The motivation given by the teacher is alsovarious motivations with rewards or directly to students (4) the role of the teacher as amanager, in online learning here the teacher acts as a learning manager, so that learningcan be directed according to the basic competencies and learning objectives that must beachieved; (5) the role of the teacher as an evaluator here, the teacher plays a role inproviding evaluations in order to find out the extent to which students master a learningmaterial. Not only is the support for inhibiting factors very diverse, teachers play a veryimportant role in the implementation of online learning in the midst of the Covid-19Pandemic